2017
DOI: 10.1039/c7ob00947j
|View full text |Cite
|
Sign up to set email alerts
|

A sialosyl sulfonate as a potent inhibitor of influenza virus replication

Abstract: A new direction for influenza virus sialidase inhibitor development was identified using a sulfonate congener of 2-deoxy-2-β-H N-acetylneuraminic acid. Sialosyl sulfonates can be synthesised efficiently in four steps from N-acetylneuraminic acid via a microwave assisted decarboxylation. The presence of the sulfonate group significantly increases inhibition of influenza virus sialidase and viral infection when compared to the carboxylate congener, and also to the benchmark sialidase inhibitor 2,3-dehydro-2-deox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Key among the interacting substituents is a charged group, represented by the carboxylate of the natural substrate, and of 1 , which contributes significantly (≥50 % of the interaction energy) to binding of the substrate or inhibitor to the enzyme active site. We, and others, have recently reported that the sialosyl α‐sulfonate 4 , with a central, saturated pyranose ring, and in which the natural carboxylate is replaced by a sulfonate group, is an inhibitor of both viral and bacterial sialidases. The incorporation of the sulfonate as the acidic group led to significantly greater inhibitory potency relative to the corresponding carboxylate and phosphonate congeners.…”
Section: Figurementioning
confidence: 93%
See 4 more Smart Citations
“…Key among the interacting substituents is a charged group, represented by the carboxylate of the natural substrate, and of 1 , which contributes significantly (≥50 % of the interaction energy) to binding of the substrate or inhibitor to the enzyme active site. We, and others, have recently reported that the sialosyl α‐sulfonate 4 , with a central, saturated pyranose ring, and in which the natural carboxylate is replaced by a sulfonate group, is an inhibitor of both viral and bacterial sialidases. The incorporation of the sulfonate as the acidic group led to significantly greater inhibitory potency relative to the corresponding carboxylate and phosphonate congeners.…”
Section: Figurementioning
confidence: 93%
“…We, and others, have recently reported that the sialosyl α‐sulfonate 4 , with a central, saturated pyranose ring, and in which the natural carboxylate is replaced by a sulfonate group, is an inhibitor of both viral and bacterial sialidases. The incorporation of the sulfonate as the acidic group led to significantly greater inhibitory potency relative to the corresponding carboxylate and phosphonate congeners. Sulfonate derivative 4 showed micromolar level inhibition of influenza virus sialidase activity and viral infection in vitro, and was more effective than the benchmark unsaturated sialidase inhibitor Neu5Ac2en 2 .…”
Section: Figurementioning
confidence: 93%
See 3 more Smart Citations